2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037865
|View full text |Cite
|
Sign up to set email alerts
|

Surface modifications of human tooth using Nd:YAG laser for dental applications

Abstract: Ablation using Nd:YAG laser has potential in resulting a rough effect on tooth surfaces. The objective of this study is to perform a comparative evaluation of the roughness structure of enamel using the Cynosure Cynergy Nd:YAG laser and 37% phosphoric acid. The results obtained for laser-etched with a pulse width of 300ms show roughed and porous surface with greater depth. Both show remarkable graininess on the surface and fewer indentations. Comparison of the elemental compositions demonstrated that calcium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The results demonstrated that the bond strength of Vertise® Flow increased up to 38% following laser irradiation compared to SiC treatment, being comparable to bond strength values in control group (OptiBond™ All-In-One and Premise™ Flowable). The authors argued that the ablation effect promoted by Er:YAG laser on enamel surface resulted in a more irregular and microretentive morphological pattern, increasing surface area for micromechanical interlocking of flowable resin composites 30 , as reported in other micromorphological studies 51,52 . Despite Er:YAG laser treatment increased the enamel bond strength of tested SAFRC, high cost and learning curve to manipulate the device makes it an unfeasible option compared to phosphoric acid etching.…”
Section: Discussionmentioning
confidence: 82%
“…The results demonstrated that the bond strength of Vertise® Flow increased up to 38% following laser irradiation compared to SiC treatment, being comparable to bond strength values in control group (OptiBond™ All-In-One and Premise™ Flowable). The authors argued that the ablation effect promoted by Er:YAG laser on enamel surface resulted in a more irregular and microretentive morphological pattern, increasing surface area for micromechanical interlocking of flowable resin composites 30 , as reported in other micromorphological studies 51,52 . Despite Er:YAG laser treatment increased the enamel bond strength of tested SAFRC, high cost and learning curve to manipulate the device makes it an unfeasible option compared to phosphoric acid etching.…”
Section: Discussionmentioning
confidence: 82%
“…Goswami and his team studied the Nd:YAG-laser-etched enamel surface, finding a surface that is similar in aspect to other laser types but with a lower shear bond strength than acid etching [ 50 ]. One study found similar effects of bond strength when comparing Nd:YAG to acid etching [ 52 ]. Contrary to this, Fuhrmann and collaborators found CO 2 and Nd:YAG lasers produced sufficient modification of enamel for bracket bonding [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the condition of the sample whether wet or dry is also examined to identify the differences outcome of the laser ablation process. This paper is an extension of work originally presented in the 39 th International Conference of IEEE Engineering in Medicine and Biology Society [19].…”
Section: Introductionmentioning
confidence: 99%